Daily Variation in Sleep Duration, Affect and Emotions in Croatian Youth: An Ambulatory Assessment - Šutić, Lucija; Novak, Miranda (European Journal of Mental Health, 2024)
Introduction: Sleep habits are related to mood stability and mental health, and adolescence may be an appropriate time to address disturbed sleep patterns because it is a critical period for the onset of psychological problems.Aims: This study had two aims, namely: to explore associations between objectively measured sleep duration and positive and negative affect, as well as specific positive and negative emotions at the within-person and between-person levels in Croatian adolescents.Methods: In the present eight-day study, 102 Croatian adolescents with an average age of 15 years reported how they felt once a day, while sleep duration was objectively measured by collecting data from an accelerometer on participants’ smartphones.Results: Multilevel analyses showed that adolescents express more positive affect (Est. = 0.10, p < .050) and feel less distracted (Est. = -0.12, p < .050) and happier (Est. = 0.11, p < .050) on days when they sleep longer, with a multiverse analysis suggesting that these results are moderately robust. In addition, they express higher levels of negative affect, stress and distraction on school days, and boys seem to experience more positive and fewer negative emotions.Conclusions: A better understanding of daily variations in sleep duration, sleep quality, and affect would promote the development of individualized, particularly smartphone-based, sleep interventions. Such interventions could be a valuable tool for preventing mental health problems in adolescence.